Dehydroepiandrosterone and Dehydroepiandrosterone Sulfate in Alzheimer's Disease: A Systematic Review and Meta-Analysis - Pan, Xiongfeng; Wu, Xinyin; Kaminga, Atipatsa C.; Wen, Shi Wu; Liu, Aizhong (Frontiers in Aging Neuroscience, 2019)
Background and Purpose: Previous studies found inconsistent results for the relationship between Alzheimer's disease and the levels of dehydroepiandrosterone and dehydroepiandrosterone sulfate. This study performed a systematic review and meta-analysis to evaluate previous studies' results on this relationship. Method: Studies related to this outcome were obtained using a systematic search from the electronic databases of PubMed, Embase, Web of Science, and Psyc-ARTICLES in March 2018. The random-effects model was used to measure the strength of the association between Alzheimer's disease and the levels of dehydroepiandrosterone and dehydroepiandrosterone sulfate, using the standardized mean difference. Results: Thirty-one eligible studies were included in the final analysis. There was no statistically significant association between the level of dehydroepiandrosterone and Alzheimer's disease (standardized mean difference: 0.51, 95% confidence interval: −0.44 to 1.45, Z = 1.06, p = 0.29). On the other hand, lower level dehydroepiandrosterone sulfate was observed in patients with Alzheimer's disease than in controls (standardized mean difference: −0.69, 95% confidence interval: −1.17 to −0.22, Z = −2.84, p < 0.01). Conclusion: Decreased dehydroepiandrosterone sulfate concentrations may be an important indicator for Alzheimer's disease, although whether dehydroepiandrosterone sulfate could be used as a diagnostic tool requires further research.